Chronic small intestinal helminth infection perturbs bile acid homeostasis and disrupts bile acid signaling in the murine small intestine - Lane, Jenna M.; Brosschot, Tara P.; Gatti, Dominique M.; Gauthier, Courtney M.; Lawrence, Katherine M.; Pluzhnikova, Victoria; Reynolds, Lisa A. (Frontiers in Parasitology, 2023)
Soil-transmitted helminths are potent manipulators of the mammalian host immune system, and do so by dampening inflammation and inducing regulatory immune pathways in order to establish chronic infections within the gastrointestinal tract (Varyani et al., 2017). Identifying the molecules which mediate helminth-driven immunomodulation is of importance for helminthinfected people and livestock animals, but in addition, may have therapeutic applications for immune-driven inflammatory disorders including inflammatory bowel diseases (Ryan et al., 2020). The majority of efforts to date have concentrated on characterizing molecules directly produced by helminths in their excretory-secretory (ES) material, which has been shown to contain protein, small RNA, and metabolite components each with demonstrated immunomodulatory effects (Yeshi et al., 2022).As well as ES material produced directly by helminths influencing immune functioning, there are profound changes to the structure and functional capabilities of the bacterial microbiota during helminth infection (Peachey et al., 2017;Llinás-Caballero and Caraballo, 2022). Together, this results in the helminth-infected gut harbouring a distinct concoction of potentially immunomodulatory molecules which differs to that present during homeostasis (Brosschot and Reynolds, 2018). Metabolites within this 'helminth-modified' intestinal environment have been shown to impact immune cell functions (Brosschot and Reynolds, 2018), although there is limited progress in both identifying the specific types of metabolites altered during intestinal helminth infection and examining the functional consequences of helminth-modified metabolites in vivo (